Cell–tissue interactions in osteoarthritic human hip joint articular cartilage. (28th April 2014) - Huttu, Mari R. J.; Puhakka, Jani; Mäkelä, Janne T. A.; Takakubo, Yuya; Tiitu, Virpi; Saarakkala, Simo; Konttinen, Yrjö T.; Kiviranta, Ilkka; Korhonen, Rami K.
Abstract: Volume and morphology of chondrocytes in osteoarthritic human hip joint articular cartilage were characterized, and their relationship to tissue structure and function was determined. Human osteochondral articular cartilage samples ( n = 16) were obtained from the femoral heads of nine patients undergoing total hip arthroplasty due to osteoarthritis (OA). Superficial chondrocytes ( N = 65) were imaged in situ with a confocal laser scanning microscope at 37 °C. This was followed by the determination of the mechanical properties of the tissue samples, depth-wise characterization of cell morphology (height, width; N = 385) as well as structure and composition of the tissues using light microscopy, digital densitometry, Fourier transform infrared microspectroscopy and polarized light microscopy. Significant correlations were found between the cell volume and the orientation angle associated with the collagen fibers ( r = 0.320, p = 0.009) as well as between the cell volume and the initial dynamic modulus of the tissue ( r = −0.305, p = 0.013). Furthermore, the depth-dependent chondrocyte aspect ratio (height/width) correlated significantly with the orientation angle of the collagen fibers and with the tissue's proteoglycan content ( r = 0.261 and r = 0.228, respectively, p < 0.001). Our findings suggest that the orientation angle of the collagen fibers primarily controls chondrocyte volume and shape in osteoarthritic human hip joint articular cartilage.